SELECTING A SCALED AGILE APPROACH FOR A FIN-TECH COMPANY - Christopher, Lauren; de Vries, Marne (The South African Journal of Industrial Engineering, 2020)
Agile methodologies were created for small co-located teams; but their benefits are now needed for projects with multiple, geographically dispersed teams. This raises the issue of scaled Agile — the modification of Agile to suit grander endeavours. This article introduces a fin-tech company which is building a digital banking platform and is already running Scrum, with the crucial need to scale its Agile approach because numerous globally distributed development teams are working on this project. A systematic inquiry at the enterprise, using interviews and surveys, raised issues about inter-team communication, collaboration, and dependencies, all of which link to issues in the literature about scaling Agile. Using a systematic process of extracting knowledge on Agile-at-scale frameworks from the literature, a comparison of existing frameworks (SAFe, Less, DAD, and Nexus) was used to determine which was best suited, with Nexus being suggested for the enterprise. We conclude by suggesting case study research to experiment further with Nexus.